ENTRE VERDAD Y SIMULACRO: LAS IMÁGENES DE LA IMAGEN EN FILOSOFÍA - Juan Cristóbal Cruz (Tópicos, 2013)
The Platonic criticism against image marked Occidental philosophy. However, different from other tradition, based on Aristotle it has been achieved, not without difficulty, to value image as media or cognitive support, and even as a creative matrix. However two circumstances joined together cause a problem to our relationship with images. On one side, the religious image and its political effects, have originated the need to look for its neutralization. On the other hand, when making of image an arbitrary sign, it repeats the Platonic mistake of separating the image of its cognitive capacity.